Keratinic amyloid deposition in canine hair follicle tumors. Issue 1 (January 2023) - Kobayashi, Kyoko; Iwaide, Susumu; Sakai, Hiroki; Kametani, Fuyuki; Murakami, Tomoaki
Keratinic primary localized cutaneous amyloidosis is a disease in humans; however, no similar condition has been reported in animals. This study aimed to investigate cutaneous keratinic amyloid deposition in dogs and elucidate its etiology. Canine hair follicle tumor tissues were histopathologically analyzed. Immunohistochemistry and mass spectrometry–based proteomic analyses were performed to identify precursor protein candidates. Structural prediction and in vitro fibrillization analyses were conducted to determine the amyloidogenic region and gene sequencing analysis was performed to assess mutations. Of the 266 samples, 16 had amyloid deposition. Amyloid deposits were found in the stroma of tumors and in the margins of keratin debris and around normal hair follicles. Cytokeratin 5 (CK5) was identified as a precursor protein candidate. C-terminal truncation of CK5 was observed in amyloid deposits, and the truncation sites varied depending on the deposition pattern. There was a significantly higher incidence of amyloid deposition in Shiba dogs, and CK5 amino acid polymorphisms were identified in these dogs. A part of the C-terminal region of both canine and human CK5 exhibited highly amyloidogenic properties in vitro. This study revealed the existence of cutaneous keratinic amyloid deposition in animals and identified CK5 as an amyloid precursor protein, providing novel insights into understanding the etiology of cutaneous amyloidosis.